Opportunities and Challenges of the State Defense Paradigm in the Era of Globalization - Laode Muhamad Fathun; Tiara Puspa Maharani; Nazaruddien Agus Salim Putra Angkotasan (The Republic of Indonesia Defense University, 2023)
In the era of globalization, efforts to defend the country no longer involve physical warfare. This study aims to describe the opportunities and challenges to defend Indonesia in the globalization era. This research was conducted because it has an urgency that there is a meaning of disruption in the paradigm of state defense in the era of globalization. This study is a descriptive-qualitative study that used library research to collect data from surveys, observations, Focus Group Discussions, and Interviews. This study finds that through the digital era, social media platforms will create interactive, communicative, and multi-channel communication dialogue patterns that will create a digital community that loves the motherland and is aware of the nation and state. Besides, the transformation of the value of State Defense in the digital era is more effective than previously. On the other side, Indonesia is still facing cultural, structural, and postural challenges. Thus, the challenges faced also need to be considered and prevented together with all existing stakeholders and state defense agents.